Answer :

joy123333

Answer:

Sydney is 44 years old.

Step-by-step explanation:

State your variables

let x be Devaughn's age

let y be Sydney's age

Write equations using information from the problem

x = y - 6               "Devaughn is 6 years younger than Sydney"      

x + y = 82                "The sum of their ages is 82"

Solve using the substitution method

Notice that the first equation equals to "x". The second equation has the letter "x". You can replace the second "x" using the expression in the first equation.

x + y = 82                   Second equation. Replace "x" with y - 6.

y - 6 + y = 82             Combine like terms (add the "y"s together)

2y - 6 = 82

Start isolating "y"

2y - 6 + 6 = 82 + 6              Add 6 to both sides

2y = 88

2y/2 = 88/2              Divide both sides by 2

y = 44                Sydney's age

Therefore Sydney is 44 years old.

If you needed Devaughn's age:

Substitute y = 44 in the first equation.

x = y - 6

x = 44 - 6         Subtract

x = 38             Devaughn's age

admil585

Answer:

76

Step-by-step explanation:

82-6=76

Other Questions